The Effectiveness of The Problem-Based Learning Model on Student Learning Achievement in Islamic Education Learning - Karisma Damayanti; Mukhlison Effendi; Rihab Wit Daryono (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2024)
Objective: This study aims to assess the effectiveness of the Problem-Based Learning (PBL) model on students' academic achievement in Islamic Education Learning in class VIII at MTs An-Nuur Trisono. Method: Using a pseudo-experimental design with a pretest-posttest control group design, the study involved two classes: one experimental group that followed Islamic Education Learning with PBL, and one control group with conventional models. Data was collected through tests covering Islamic Education Learning's subject matter. Results: Statistical analysis showed a significant increase in students' learning outcomes using PBL (65.6%) compared to the conventional model (41.2%). Novelty: Students who engaged in PBL learning showed better concept understanding, application of moral values, and problem-solving skills. This study provides empirical support for the effectiveness of PBL in improving Islamic Education Learning's learning outcomes. The implications of this study emphasize the importance of applying innovative learning models such as PBL to improve the quality of Islamic religious education in secondary schools. The findings will guide teachers, schools, and education stakeholders in developing more effective learning approaches.